My Body My Message: Understanding Socio-Cultural Perspectives On Body Piercing In Contemporary Literature (Journal of Namibian Studies : History Politics Culture, 2022)
Piercing is an ancient form of body modification that has been practiced by humans for thousands of years. The act of piercing the body involves making a hole in the skin or other body parts and inserting jewelry. This act is a prevalent trend in contemporary culture, and can be associated with the socio-cultural need for self-expression, rebellion, and identity formation. Body piercing thus is no longer an ancient practice for spiritual or tribal initiation ceremonies, or as a sign of personal identity; it has become a way of expressing oneself in this digital world. Through this way, body piercing can be understood as a posthumanist phenomenon that challenges the traditional boundaries between human and non-human. It represents a shift towards embodying posthumanist ideals of fluidity, hybridity, and transformation. The integration of digital technology into the practice of body piercing enhances its transformative potential, allowing for new forms of artistic expression and self-representation. This paper investigates how body piercing is portrayed in contemporary literature and what insights these representations provide regarding the socio-cultural context. The paper also examines the digital implications of body modification, exploring how it is linked to issues such as gender, sexuality, power, and social conformity.